Transforming Postoperative Care Into Mobile Health Trends and Research Directions: A Bibliometric Analysis - Çankaya, Askeri; Özsoy, Hatice; Özkan, Esra; Yavuz van Giersbergen, Meryem (W.B. Saunders, 2026)
Purpose The aim of this study is to identify current themes and research trends by reviewing the research published in the literature on mobile applications in postoperative patient care. Design Descriptive and bibliometric analyses were used. Methods This study used the Web of Science (WoS) database to conduct a comprehensive literature review on October 24, 2024. A total of 108 articles meeting the inclusion criteria were analyzed. Data analysis was performed using MS Excel for forecasting, the RStudio Bibliometrix package for bibliometric analysis, and VOSviewer for data visualization. Findings A bibliometric analysis of 108 articles published between 2011 and 2024 revealed that 65.74% of the studies were published in the last 5 years. Journals in health, surgery, nursing, and informatics have led the dissemination of research on this topic. Key author keywords included "mHealth," "telemedicine," and "eHealth." The United States emerged as the most prolific and cited contributor to the field, followed by Canada in productivity and the Netherlands in citations. Conclusions The study highlights an annual growth rate of 22.51% in publications and forecasts an increase in research in this field. The integration of mobile applications in postoperative care has empowered patients, improved health outcomes, enhanced the efficiency of health care services, and contributed to cost reductions. However, as technology continues to permeate health care, further research is needed to optimize the efficacy and usability of mHealth applications in postoperative patient care. © 2026 The American Society of PeriAnesthesia Nurses.
Keywords: bibliometric analysis; mHealth; mobile application; patient engagement; postoperative care